Pengaruh Kepemimpinan Otentik Terhadap Kinerja Pegawai Dengan Komitmen Organisasional Sebagai Variabel Mediasi - Helina Pratamasari, Linda; Puryandani, Siti (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
The purpose of this study is to analyze the influence of authentic leadership and organizational commitment on the performance of village officials in the Kec.Kedungtuban area. In this study using quantitative methods and data techniques using PLS operated through Smart PLS 3.0 software. The sample selection method uses saturated samples. The respondents in this study were village tools in the Village Government in the Kec Kedungtuban Region with a total of 172 people. Data collection in this study was carried out using an online questionnaire. The online questionnaire was sent to respondents via WhatsApp number. Based on the results of data analysis, it was concluded that authentic leadership has a significant effect on organizational commitment and employee performance, organizational commitment has a significant effect on employee performance and organizational commitment is able to play a mediation between authentic leadership and employee performance.